Energy demand in soybean seeding on maize straw intercropped with forage - Chioderoli, Carlos A.; Silva, Vicente F. A.; Furlani, Carlos E. A. [UNESP]; Bertonha, Rafael S. [UNESP]; Cavichioli, Fabio A. [UNESP] (Departamento de Engenharia Agrícola - UFCG, 2014)
The sustainability of no-tillage system is fully linked to the soil use and management, in order to use technologies that promote the accumulation of dry vegetation in the soil, but it may affect the performance of agricultural machinery. Therefore, the objective of this study was to evaluate in soybean seeding the operational performance of tractor-seeder on maize straws intercropped with Urochloas in different treatments. The study was conducted in a randomized block design in factorial scheme 2 x 4 + 1, with four replications, formed by two intercropped forage species and five cropping systems. The dry maize straw, Urochloas dry mass and total straw dry mass were determined in treatments to verify the operational performance of the machines. The results showed that the amount of straw produced by maize and Urochloas interferes with the slippage of the tractor s front wheels, i.e., areas with higher amount of straw promotes lower adherence of the wheel. Energy demand was not affected by amount of straw produced by the treatments, as well as fuel consumption and operational field capacity.

A sustentabilidade do sistema plantio direto está ligada ao uso e ao manejo do solo com o propósito de utilizar tecnologias que promovam o acúmulo de massa seca vegetal no solo porém podem afetar o desempenho das máquinas agrícolas. O objetivo deste trabalho foi avaliar, na semeadura da soja, o desempenho operacional do conjunto trator-semeadora sobre palhadas de milho consorciado com Urochloas em diferentes tratamentos. A pesquisa foi instalada em blocos casualizados em esquema fatorial 2 x 4 + 1, com quatro repetições, formados pelo consórcio de duas espécies forrageiras em cinco sistemas de cultivo. A massa seca de palha do milho, massa seca de Urochloas e massa seca total de palha foi determinada nos tratamentos para verificar o desempenho operacional das máquinas. Os resultados demonstraram que a quantidade de palha produzida pelo consórcio de milho com Urochloas interfere na patinagem dos rodados dianteiros do trator, ou seja, áreas com maior quantidade de palha promovem menor aderência dos rodados. A demanda energética não é afetada pela quantidade de palha produzida pelos tratamentos tal como o consumo de combustível e a capacidade de campo operacional.
Demanda energética na semeadura de soja sobre palha de milho consorciado com forrageiras
Keywords: sistema plantio direto; patinagem dos rodados; integração lavoura-pecuária; no tillage system; slippage of wheels; crop-livestock integration